Intrarenal Determinants of GFR Decline During Loop Diuretic Therapy - Negiin Pourafshar; Chanwoo Nam; Siddharth S. Madapoosi; Michael J. Choi; Salim Shah; Bertram Pitt; Lingyun (Ivy) Xiong; Patrick Rossignol; Robert Unwin; Jeffrey Testani; Christopher S. Wilcox (Hypertension, 2026)
Loop diuretics are first-line therapy for hypervolemia. They block the sodium-potassium-2-chloride cotransporter type 1 on the renal afferent arteriole that mediates vasoconstriction and the sodium-potassium-2-chloride cotransporter type 2 on the macula densa cells that mediates the tubuloglomerular feedback response and raises intrarenal pressure that inhibits the myogenic response. These should reduce afferent arteriolar vasoconstriction and increase the glomerular filtration rate; however, more often, the glomerular filtration rate is reduced. This has been attributed to diuretic-induced extracellular volume depletion that activates a systemic neurohormonal response. Accordingly, a fall in glomerular filtration rate can lead to strategies to restore body fluid volumes while reducing the diuretic dosage. Here, we review the regulation of renal hemodynamics during loop diuretic therapy. We propose that a passive, obstructive component of reduced renal blood flow combines with activation of renal afferent nerves, macula densa–derived renin release with intrarenal Ang II (angiotensin II) formation, and generation of vasoconstrictor prostaglandins and thromboxane to provide intrarenal mechanisms of passive and active increases in renal vascular resistance that together can reduce the glomerular filtration rate. The hypothesis that a reduction in the glomerular filtration rate with loop diuretics can derive from intrarenal mechanisms of vasoconstriction rather than from volume depletion suggests novel approaches to manage diuretic resistance and worsening renal function in heart failure.